Evidence of local adaptation despite strong drift in a Neotropical patchily distributed bromeliad - Leal, Barbara Simoes Santos [UNESP]; Chaves, Cleber Juliano Neves [UNESP]; Graciano, Vanessa Araujo [UNESP]; Boury, Christophe; Huacre, Luis Alberto Pillaca; Heuertz, Myriam; Palma-Silva, Clarisse [UNESP] (Springer, 2021)
Both genetic drift and divergent selection are predicted to be drivers of population differentiation across patchy habitats, but the extent to which these forces act on natural populations to shape traits is strongly affected by species' ecological features. In this study, we infer the genomic structure of Pitcairnia lanuginosa, a widespread herbaceous perennial plant with a patchy distribution. We sampled populations in the Brazilian Cerrado and the Central Andean Yungas and discovered and genotyped SNP markers using double-digest restriction-site associated DNA sequencing. In addition, we analyzed ecophysiological traits obtained from a common garden experiment and compared patterns of phenotypic and genetic divergence (P-ST-F-ST comparisons) in a subset of populations from the Cerrado. Our results from molecular analyses pointed to extremely low genetic diversity and a remarkable population differentiation, supporting a major role of genetic drift. Approximately 0.3% of genotyped SNPs were flagged as differentiation outliers by at least two distinct methods, and Bayesian generalized linear mixed models revealed a signature of isolation by environment in addition to isolation by distance for high-differentiation outlier SNPs among the Cerrado populations. P-ST-F-ST comparisons suggested divergent selection on two ecophysiological traits linked to drought tolerance. We showed that these traits vary among populations, although without any particular macro-spatial pattern, suggesting local adaptation to differences in micro-habitats. Our study shows that selection might be a relevant force, particularly for traits involved in drought stress, even for populations experiencing strong drift, which improves our knowledge on eco-evolutionary processes acting on non-continuously distributed species.